Exploring the effect of the Group Size and Feedback of non-player character spectators in virtual reality exergames - Xu, Wenge; Yu, Kangyou; Meng, Xuanru; Monteiro, Diego; Kao, Dominic; Liang, Hai-Ning (Frontiers in Psychology, 2023)
Virtual spectators, using non-player characters (NPCs), have been widely adopted in commercial video games. However, the impact of their presence and feedback on players' performance and experience has not been widely studied, especially in virtual reality (VR) exergames. This paper aims to fill this gap and reports two user studies that assess their effect on such games. Study 1 explored the impact of having spectator NPCs present and their feedback available in gesture-based VR exergame and found having virtual spectators and their feedback could improve players' game performance, experience, and exertion. Based on the results of Study 1, we further explored two characteristics of the spectators—their size (small/large) and their feedback (with/without). The results show that (1) a large spectator number is more helpful since it improves the overall game experience (higher competence, flow, immersion), increases AvgHR%, and enhances performance (improved players' combo performance and increased gesture success rate for particular gesture); (2) spectator feedback is instrumental in improving players' performance (higher gesture success rates, more combos performed successfully, more monster's combos prevented), enhancing game experience (positive affect, competence, flow, and immersion), and reducing negative game experience, increasing exertion (AvgHR% and burned more calories). Based on the results, we derived two main design recommendations for VR exergames that could pave the way for improving gameplay performance and game experience, especially among young adults.